Advances in intraoperative imaging in retinal diseases: A narrative review - Jorge Rocha; Raphaela M. Fuganti; Antonio M. Casella (Taiwan Journal of Ophthalmology)
This review explores recent technological advances in intraoperative imaging during retinal disease surgeries, focusing on their applicability in clinical practice and impact on surgical outcomes. A literature search identified studies discussing new imaging technologies, their advantages over conventional methods, relevant case studies, and literature reviews. Exclusion criteria included studies unrelated to retinal diseases, imaging technologies not suitable for intraoperative use, outdated articles, and nonscientific reports. Significant advancements, particularly with optical coherence tomography (OCT), have transformed retinal surgery by providing high-resolution images and real-time feedback, enhancing surgical precision and patient safety. However, the high costs of these technologies remain a barrier to widespread adoption, despite their potential to set new standards in ophthalmic surgery.